2014
DOI: 10.2147/ott.s70012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of advanced and metastatic renal cell carcinoma treated with targeted therapy: is there a difference between young and old patients?

Abstract: BackgroundTo assess whether the clinical outcome of advanced and metastatic renal cell carcinoma (mRCC) treated with targeted therapy differs between young and old patients.Patients and methodsA total of 327 patients with advanced renal cell carcinoma and mRCC who received targeted therapy in two Chinese clinical centers were analyzed retrospectively. The patients were stratified into three groups: young (aged <45 years), middle-aged (aged 45–64 years), and old (aged ≥65 years). Overall survival (OS) and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The results of our study were consistent with reported data from a small sampling of Chinese patients, which were little different from other Asian non-Chinese data. 9 , 18 In a Japanese study, they found that the median PFS was 7.4 months, the median OS was 25.3 months, and these results were also longer than that in the TARGET study. 19 Some results from another Japanese study showed that the median PFS was 9.0 months and sorafenib was effective in Japanese patients with advanced renal cell cancer in general clinical practice.…”
Section: Discussionmentioning
confidence: 94%
“…The results of our study were consistent with reported data from a small sampling of Chinese patients, which were little different from other Asian non-Chinese data. 9 , 18 In a Japanese study, they found that the median PFS was 7.4 months, the median OS was 25.3 months, and these results were also longer than that in the TARGET study. 19 Some results from another Japanese study showed that the median PFS was 9.0 months and sorafenib was effective in Japanese patients with advanced renal cell cancer in general clinical practice.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, uncertainties exist about the prognostic effect of age on RCC. Some authors have pointed out that older age is correlated with a higher stage and pathological grade, suggesting an adverse association with prognosis [50]. In their study, Zhang et al found that younger patients with mRCC receiving targeted therapy had a poorer prognosis compared with older patients [50].…”
Section: Discussionmentioning
confidence: 97%
“…Some authors have pointed out that older age is correlated with a higher stage and pathological grade, suggesting an adverse association with prognosis [50]. In their study, Zhang et al found that younger patients with mRCC receiving targeted therapy had a poorer prognosis compared with older patients [50]. Interestingly, the mean age of patients receiving axitinib, cabozantinib, nivolumab, and the combination of everolimus plus levatinib was < 65 years.…”
Section: Discussionmentioning
confidence: 97%
“…Stage IV/metastatic renal cell carcinoma (mRCC) has been historically associated with a poor prognosis. Nonetheless, outcomes in metastatic disease are not uniform and are influenced by both patient and disease factors (4,5). Existing risk stratification systems including Memorial Sloan Kettering Cancer Center (MSKCC)/Motzer criteria and International Metastatic RCC Database Consortium (IMDC)/Heng criteria staging have sought to stratify metastatic heterogeneity by incorporating clinical and laboratory data into prognostic groupings (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%